Structure and Magnetic Properties of an Original CuIIMnIIWV Heterotrimetallic Coordination Polymer. Issue 32 (9th July 2020) - Alexandru, Maria‐Gabriela; Visinescu, Diana; Madalan, Augustin M.; Clérac, Rodolphe; Andruh, Marius
Abstract : A monodimensional heterotrimetallic coordination polymer of formula ∞ 1 [Cu II Mn II L 2 3 (µ‐NC)3 W V (CN)5 2 ]· H2 O (1 ) has been assembled from pre‐designed [Cu II Mn II L 2 ] 2+ cationic modules and homoleptic [W V (CN)8 ] 3– metalloligands (H2 L 2 is the compartmental Schiff‐base resulting from the stepwise condensation of 2, 6‐diformyl‐ p ‐cresol with ethylenediamine and diethylenetriamine). The magnetic properties of 1 have been investigated revealing a three‐dimensional ordered antiferromagnetic ground state below 4 K resulting from different antiferromagnetic interactions between all the spin carriers ( S = 1/2 Cu II, S = 5/2 Mn II, and S = 1/2 W V centers). Abstract : A heterotrimetallic coordination polymer, with an accordion‐like topology and a three‐dimensional ordered antiferromagnetic ground state, has been assembled from Cu II Mn II binuclear modules and W V (CN)8 metalloligands.